Gram-Negative Bacterial Lysins - Ghose, Chandrabali (Antibiotics (Basel), 2020)
Antibiotics have had a profound impact on human society by enabling the eradication of otherwise deadly infections. Unfortunately, antibiotic use and overuse has led to the rapid spread of acquired antibiotic resistance, creating a major threat to public health. Novel therapeutic agents called bacteriophage endolysins (lysins) provide a solution to the worldwide epidemic of antibiotic resistance. Lysins are a class of enzymes produced by bacteriophages during the lytic cycle, which are capable of cleaving bonds in the bacterial cell wall, resulting in the death of the bacteria within seconds after contact. Through evolutionary selection of the phage progeny to be released and spread, these lysins target different critical components in the cell wall, making resistance to these molecules orders of magnitude less likely than conventional antibiotics. Such properties make lysins uniquely suitable for the treatment of multidrug resistant bacterial pathogens. Lysins, either naturally occurring or engineered, have the potential of being developed into fast-acting, narrow-spectrum, biofilm-disrupting antimicrobials that act synergistically with standard of care antibiotics. This review focuses on newly discovered classes of Gram-negative lysins with emphasis on prototypical enzymes that have been evaluated for efficacy against the major antibiotic resistant organisms causing nosocomial infections.